The impact of a comprehensive physical, mental and spiritual programme on fall risk, physical fitness and blood pressure in elderly residents of nursing homes: An RCT Study: 10.55131/jphd/2024/220118 - Suratih, Kanthi; Budi Cahyanto, Erindra; Mulyani, Sri; Azmiardi, Akhmad (Journal of Public Health and Development, 2024)
As bodily functions decline, older people encounter various challenges in physical, mental and social well-being, for example risk of falls, hypertension and depression. Physical exercise is among the most recommended solutions to address the issues faced by the elderly. This study aimed to evaluate a holistic programme incorporating diverse physical exercises (aerobic exercise, muscle strength, flexibility), combined with mental and spiritual practices (breathing relaxation and gratitude) in reducing fall risk, enhancing physical fitness, and regulating blood pressure, in elderly residents of nursing homes. The study employed a Cluster Randomised Controlled Trial design in Surakarta, Indonesia. Seventy-one participants were randomly assigned to either the intervention group (n=42) or control groups (n=29). The intervention group engaged in the programme three times per week, for 60 minutes per session, over 16 weeks. The control group continued their routine activities, including sunbathing or other relaxing pursuits. In the fall risk variable, the intervention group exhibited a higher mean score than the control group, specifically 49.79 ±2.70 compared to 46.21 ±3.16, p=0.05, while for physical fitness, 60.24 ±7.65 compared to 49.57 ±11.66, p=0.05. Concerning systolic blood pressure, the mean value for the intervention group was 146.11 ± 20.07, while the control group was 148.59 ± 23.20, p = 0.63. The intervention group recorded a mean value of 84.10 ± 13.75 for diastolic blood pressure, whilst the control group recorded 86.25 ± 9.83, p = 0.98. This research underscored the influence of SPIRIT programme on reducing fall risk and enhancing physical fitness in elderly nursing home residents, although it is not effective in lowering blood pressure. Elderly people in nursing homes and communities can consider the SPIRIT programme as an attempt to prevent non-communicable diseases. Additional research is recommended to explore the impact of this programme on the blood pressure of older people.